Professional Challenges of Medical Social Work in the Safe Discharge of Patients A Qualitative Study - Ahmad Kalateh Sadati; Seyed Reza Javadian; Marzieh Sadeghi Hardangi (Tehran University of Medical Sciences, 2023)
Background and Purpose: Discharge planning, as a process for the safe transfer of patients, has always been challenged by the interventions of medical social workers. Identifying these challenges prevents disruptions in effective planning. This research aims to explore the challenges faced by medical social workers in discharge planning. Materials and Methods: This is a qualitative study conducted in Iran in 2023. Data were collected through semi-structured face-to-face and telephone interviews with 16 social workers working in hospitals and were manually analyzed using thematic analysis. Results: The findings of this study revealed that hospital social workers encounter structural and professional challenges during discharge planning. As a result, themes such as professional isolation, erosive environment, back-breaking costs, inefficient structures, and professional pressures were identified, with the main theme being unattended discharge. Conclusion: The results indicate that social workers in hospitals are faced with poor cooperation and participation, a lack of facilities and equipment, and socio-economic barriers at the community level. They encounter professional challenges in adhering to professional principles and values and in maintaining the quality of social work services in discharge planning. Given the importance of post-discharge interventions, organizational, structural, and professional reforms at both the micro and macro levels are recommended.